LOGICAL ANALYSIS IN THE ARGUMENTATION SYSTEM "PHILOSOPHY OF LANGUAGE" - Комаха, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The paper reveals a problem of forming a system of argumentation in the process of new thinking development in analytical philosophy. A new "image" of logic is investigated in the concepts of the Vienna Circle representatives, who sought the most productive ways to prove the truth in scientific knowledge. Directions of a new system of argumentation are shown in a situations of change of logical analysis techniques, which took place on two areas – logic and language.